"The First Intervention Is Leaving Home": Reasons for Electing an Out‐of‐hospital Birth among Minnesotan Mothers. (1st June 2017) - Hazen, Helen
Abstract: The Twin Cities (Minneapolis–St. Paul), Minnesota, has seen a recent increase in the number of mothers seeking an out‐of‐hospital birth. This research uses in‐depth interviews with 24 mothers who intended an out‐of‐hospital birth in the previous two years, exploring their reasons for pursuing an alternative approach to birth. For many women, an out‐of‐hospital birth fits within a philosophy that rejects the pathologizing of birth. Escaping rigid hospital protocols is seen as critical to avoiding what many mothers described as unnecessary interventions. In addition, homebirth midwives are perceived as offering more holistic care for the expectant and new mother. Home itself is seen as providing a more pleasant and calm, family‐friendly atmosphere than a hospital, helping the mother relax, with the expectation that this will expedite labor. Many of the recommendations developed here have applicability to improving hospital birth experiences as well as furthering our understanding of out‐of‐hospital birth.